Competition and chaos : U.S. telecommunications since the 1996 Telecom Act - Crandall, Robert W. (Brookings Institution Press, 2005)
"Examines how the 1996 Telecommunications Act and its antecedents have affected the major telecommunications providers and analyzes the act's effect on economic welfare in the United States"--Provided by publisher
Keywords: United States. -- Telecommunications Act of 1996.; United States.; Telecommunications Act of 1996 (United States); Telecommunication policy -- United States.; Telecommunication -- Deregulation -- United States.; Competition -- Government policy -- United States.; Telecommunication -- Law and legislation -- United States.; Télécommunications -- Politique gouvernementale -- États-Unis.; Télécommunications -- Déréglementation -- États-Unis.; BUSINESS & ECONOMICS -- Industries -- Media & Communications.; TECHNOLOGY & ENGINEERING -- Telecommunications.; Competition -- Government policy; Telecommunication -- Deregulation; Telecommunication -- Law and legislation; Telecommunication policy; United States